Isokinetic performance of knee extensors and flexors in adolescent male soccer athletes - Bonetti, L. V.; Floriano, L. L.; dos Santos, T. A.; Segalla, F. M.; Biondo, S.; Tadiello, G. S. (Sport Sciences for Health, 2017)
Background: Soccer is one of the most popular sports in the world and thigh muscle strain and knee injuries are two of the most common injuries. Asymmetrical muscle strength between the dominant limb (DL) and the non-dominant limb (NDL), asymmetries between the extensor and flexor muscles of the knee and between the different roles can explain the high injury incidence. Aims: This study aimed to analyze the knee extensor and flexor muscular contralateral strength, the flexors`/extensors` function, and the muscular strength differences according to different playing positions of adolescent male soccer athletes. Methods: The information provided by the database concerning the isokinetic evaluation of knee muscles from 32 male soccer athletes under 17 years of age was analyzed. The isokinetic dynamometer was used in a concentric-concentric mode for the knee extensor and flexor muscles at angular velocities of 60°/s, 120°/s, 180°/s and 240°/s. Results: Two significant differences were observed between the DL and the NDL; just at an angular velocity of 60º/s, the flexor muscles and the flexor/extensor ratio mean values were significantly smaller for the NDL. When averaged separately, the DL and NDL values of the defenders, midfielders, and forwarders demonstrated no differences in the peak torque and flexor/extensor analysis. Conclusions: Muscular demands of adolescent soccer players do not cause large asymmetries and imbalances in the extensors and flexor muscles of the knee. In addition, different soccer playing positions do not significantly affect peak torque and flexor/extensor ratio results.